PENGARUH RELIGIUSITAS, LEADERSHIP DAN BUDAYA ORGANISASI TERHADAP PENCEGAHAN FRAUD PADA EKOWISATA MANGROVE - carolina, anita; fajariyah, dianatul (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of religiosity, leadership, and organizational culture on fraud prevention in Madura mangrove ecotourism. This research is a quantitative study using primary data through the distribution of questionnaires to the community and mangrove tourism actors. The determination of the sampling technique in this study was carried out by purposive sampling, namely where the sample members of the population used certain classifications (Community, and tourism actors except for the head of tourist attractions), which were analyzed using multiple linear regression analysis with the help of SPSS Ver. 21. The results showed that religiosity, leadership, and organizational culture have a positive effect on fraud prevention in Madura.